p53 determines prognostic significance of the carbohydrate stem cell marker TF1 (CD176) in ovarian cancer - Heublein, Sabine (Journal of cancer research and clinical oncology, 2016)
IntroductionThe oncofoetal Thomsen-Friedenreich (TF1, CD176) epitope is a carbohydrate cancer stem cell (CSC) antigen, and TF1-mediated cancer progression can be widely reversed by anti-TF1 antibodies. Particularly, CSC-like cells are regarded to be tumorigenic and chemoresistant. Aberrant p53 is probably the factor most closely associated with chemoresistance and tumour aggressiveness in ovarian tumours. We thus questioned whether TF1 in combination with p53 or as a single marker may be related to clinico-pathological features and survival of ovarian cancer patients.Patients and Methods Both markers were quantified in ovarian cancer tissue (n = 151) by immunohistochemistry. p53 staining was subdivided into three subgroups [n (completely negative) = 57, n (moderately stained) = 28, n (overexpressing) = 66]. TF1 was scored as positive (n = 30) versus negative (n = 121).Results Only in those cancers classified with moderate p53 staining—and thus most likely displaying with wild-type TP53—TF1 positivity turned out to be a predictor for shortened overall survival (univariate: p < 0.001, multivariate: p = 0.001). By screening 17 different protein markers for correlation with TF1, only mucin-1 emerged as a potential TF1 carrier protein.ConclusionIt is hypothesized that TF1 may confer tumour-promoting features, especially in a TP53 wild-type genetic background. In addition, TF1 is an attractive immunotherapeutic target. Whether those cases classified as TF1 positive and at the same time as moderately stained for p53 might particularly benefit from a future anti-TF1 antibody treatment or from TF1 vaccination therapy remains to be determined.